A Positive Feedback Loop of BBX11–BBX21–HY5 Promotes Photomorphogenic Development in Arabidopsis - Zhao, Xianhai (Plant Commun, 2020)
Light is the most important environmental factor affecting many aspects of plant development. In this study, we report that B-box protein 11 (BBX11) acts as a positive regulator of red light signaling. BBX11 loss-of-function mutant seedlings display significantly elongated hypocotyls under conditions of both red light and long day, whereas BBX11 overexpression causes markedly shortened hypocotyls under various light states. BBX11 binds to the HY5 promoter to activate its transcription, while both BBX21 and HY5 associate with the promoter of BBX11 to positively regulate its expression. Taken together, our results reveal positive feedback regulation of photomorphogenesis consisting of BBX11, BBX21, and HY5, thus substantiating a transcriptional regulatory mechanism in the response of plants to light during normal development.